AN ANALYSIS OF QUALITY MAXIM IN THE PROCESS OF THESIS GUIDANCE FOR ENGLISH EDUCATION DEPARTMENT STUDENTS OF UNIVET BANTARA SUKOHARJO - Purwani Indri Astuti; Giyatmi Giyatmi; Sihindun Arumi; Veronika Unun Pratiwi (Universitas Veteran Bangun Nusantara, 2019)
The objectives of this research were 1) to classify types of quality maxim, 2) to describe the types of quality maxim violation in the dialogue between students and lecturers in the process of thesis guidance.This research belongs to qualitative research. The data were all dialogues between lecturers and students having quality maxim (either violating or obeying), while the data source was the lecturers and students in the process of thesis guidance itself. This research used two kinds of data collection method, they were documentation and content analysis. The instruments were tape recorder and data cards, while the methods of data analysis were reduction, display and verification.After having analysis, it could be seen that the results of this research were type of qualitymaxim: obeying maxim and violating maxim. The violations were in the field of content(material), methodology and writing system.